“Proyecto para la creación de una guardería en la Ciudad de Loja” - Rodríguez Piedra, María Gabriela (2021)
The economy of families in Ecuador and especially in the Loja canton is basic, which is why it is necessary for father and mother to work, thus creating the need to leave their children in the care of third parties. Therefore, based on the existing need, a business idea is created, such as the creation of a Child Development Center (CDI). The general objective of this project is to carry out a project for the creation of a children's center in the City of Loja, for which a market study, a technical study, a financial study and a financial evaluation were carried out for the creation of the center " Chiquitines ” in the City of Loja. To carry out the research, methods such as the Inductive, Deductive, Statistical and Analytical-Synthetic method were used; in the same way, techniques such as Bibliography and the survey technique were used. In addition, to carry out the survey, a sampling was carried out because the population was infinite, from which a resulting sample of 397 people was obtained. In the results, the analysis and tabulation of 397 surveys applied to the families of Loja (applicants) is presented, among them 65 are men and 332 women. In addition, it was evidenced based on the surveys carried out, the acceptance of the service by potential clients and therefore the viability to execute this project. Finally, it is concluded that 78% of families correspond to effective demand, 91% represent real demand and 96% constitute effective demand. Likewise, the nursery will have a capacity for 60 children, who will be distributed in three classrooms and will be located in the La Argelia sector of the city of Loja. The total amount of the investment will be $ 22,273.37, where 45% will be financed through a loan and 55% will be equity capital. In addition, the unit cost of the monthly service will be $ 91.63 with a profit margin of 30% resulting in a monthly service sale price of $ 120.00 and a total income of $ 86,760.00. A positive NPV of $ 62,709.36 was obtained, the IRR is 85.08%, the benefit-cost ratio indicates that for every dollar invested, the company will obtain a return of 0.45 US cents and the capital will be recovered in 1 year, 4 months.